Development of a library of laminin-mimetic peptide hydrogels for control of nucleus pulposus cell behaviors. (June 2021) - Speer, Julie E; Barcellona, Marcos N; Lu, Michael Y; Zha, Zizhen; Jing, Liufang; Gupta, Munish C; Buchowski, Jacob M; Kelly, Michael P; Setton, Lori A
The nucleus pulposus (NP) of the intervertebral disc plays a critical role in distributing mechanical loads to the axial skeleton. Alterations in NP cells and, consequently, NP matrix are some of the earliest changes in the development of disc degeneration. Previous studies demonstrated a role for laminin-presenting biomaterials in promoting a healthy phenotype for human NP cells from degenerated tissue. Here we investigate the use of laminin-mimetic peptides presented individually or in combination on a poly(ethylene) glycol hydrogel as a platform to modulate the behaviors of degenerative human NP cells. Data confirm that NP cells attach to select laminin-mimetic peptides that results in cell signaling downstream of integrin and syndecan binding. Furthermore, the peptide-functionalized hydrogels demonstrate an ability to promote cell behaviors that mimic that of full-length laminins. These results identify a set of peptides that can be used to regulate NP cell behaviors toward a regenerative engineering strategy.